Różewicz and Bonhoeffer. On the Margin of the Poem Learning to Walk by Tadeusz Różewicz - Dakowicz, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The departure point of the analysis presented in this article is a poem written by Tadeusz Różewicz learning to walk (nauka chodzenia). The protagonist of the poem is Dietrich Bonhoeffer, who created the theory of “religionless Christianity”. According to Bonhoeffer, a modern Christian has to immerse himself/herself in the “godless” world so that – in tandem with the Saviour – he/she can be experience the final abandonment. The author of this article tries to prove that the theology of Bonhoeffer had a great impact on Różewicz, making him reconsider his viewpoint on faith. Due to Dietrich Bonhoeffer, the poet also found a solution for a basic contradiction that was explicated in the famous poem entitled Bez (Without): “life without god is possible / life without god is impossible”.